К фауне водяных жуков Ростовской области - Миноранский, В.А.; Джумайло, Н.Б. (Вестник зоологии, 1974)
In the territory of the Rostov Region 89 species of water beetles are registered belonging to the families Haliplidae, Gyrinidae, Hydrophilidaie and Dytiscidae. 68 species of then are mentioned for the first time for this region. The data are presented on species composition and a relative number of water beetles in different types of water bodies. In the fauna of water beetles of the region the palearctic (29.27%) and European- Siberian (35.36%) species predominate; holarctic (9.77%), Mediterranean (19.51%), steppe (3.66%) and paleotropical (2.43%) species are less numerous here.